Epigenotoxicity: a danger to the future life. Issue 4 (21st March 2023) - Kefayati, Farzaneh; Karimi Babaahmadi, Atoosa; Mousavi, Taraneh; Hodjat, Mahshid; Abdollahi, Mohammad
Abstract: Environmental toxicants can regulate gene expression in the absence of DNA mutations via epigenetic mechanisms such as DNA methylation, histone modifications, and non-coding RNAs' (ncRNAs). Here, all three epigenetic modifications for seven important categories of diseases and the impact of eleven main environmental factors on epigenetic modifications were discussed. Epigenetic-related mechanisms are among the factors that could explain the root cause of a wide range of common diseases. Its overall impression on the development of diseases can help us diagnose and treat diseases, and besides, predict transgenerational and intergenerational effects. This comprehensive article attempted to address the relationship between environmental factors and epigenetic modifications that cause diseases in different categories. The studies main gap is that the precise role of environmentally-induced epigenetic alterations in the etiology of the disorders is unknown; thus, still more well-designed researches need to be accomplished to fill this gap. The present review aimed to first summarize the adverse effect of certain chemicals on the epigenome that may involve in the onset of particular disease based on in vitro and in vivo models. Subsequently, the possible adverse epigenetic changes that can lead to many human diseases were discussed.